Perceptions of interprofessional collaboration in education of dentists and dental hygienists and the impact on dental practice in the Netherlands: A qualitative study. (15th November 2019) - Kersbergen, Maria J.; Creugers, Nico H. J.; Hollaar, Vanessa R. Y.; Laurant, Miranda G. H.
Abstract: Introduction: The purpose of this study was to evaluate the perceptions of dentists and dental hygienists regarding their own and each other's roles in interprofessional collaboration following a clinical interprofessional educational programme (CIEP) as part of their graduate programme at Radboud university medical center (Radboudumc) and HAN University of Applied Sciences (HAN UAS), Nijmegen, the Netherlands, respectively. Perceptions were obtained at the end of their study (2014) and two years after their graduation (2016). Methods: A qualitative study was conducted using a questionnaire with open‐ended questions. Sixty‐two dentists and thirty‐eight dental hygienists were invited. Theory‐based analyses were applied in combination with principles of Grounded Theory to analyse and synthesise the collected data from the open‐ended questions. Results: At baseline, 100% responded. At follow‐up, thirty‐two dentists (51.6%) and twenty‐six dental hygienists (68.4%) responded; twenty‐seven dentists (43.5%) and eighteen dental hygienists (47.4%) were included. Many similarities were found between baseline and follow‐up regarding perceptions of each other's expertise and responsibility, learning from and with each other, and the behaviour of students and the "novice" professionals in interprofessional collaboration. Both dentists and dental hygienists experienced the CIEP as useful for interprofessional collaboration. The "novice" dentists and dental hygienists indicated that in dental practices interprofessional collaboration was less common. Conclusion: The CIEP resulted in more understanding amongst dentists and dental hygienists with regard to interprofessional roles, but in practice the "novice" dentists and dental hygienists face difficulties in applying the interprofessional roles.